Sona Gelen Edatlarla Teşkil Edilen Bir Kelime Grubu : Kuvvetlendirme Grubu - Tören, Hatice (Kitabevi, 2002)
The postpositions are used as a strengthening expression in all cycles of Turkish- after both the names and the verb declensions. We frequently observe such a usage in a manner to emphasize, reinforce a name or verb as it is used after such name or verb. That is to say, the postpositions in both expressions relate to the preceding words and are used as a whole in syntax with those words in terms of structure and meaning. The structures in which the names and conjugated verbs are used together with the postpositions with strengthening function have not been considered as an independent group of words in the Turkish grammar books written until now and in various studies on syntax, not they have been assessed within other word groups. However, such structures have the characteristics of a word group both in terms of usage and meaning.
A Word Group Formed By Postpositions: Strengthening Group
Keywords: Word Groups; Postpositions; Strengthening Group; Strengthening Postpositions